Interest Linkages Among Offshore Funds - Hou, Zhenxing (2006)
This paper examines interest rate linkages among the offshore market. The data collected are daily observations of 7-day and 1-month maturity yields on the four euro-currencies interest rates, These euro-currencies are euro-USD (United States), euro-GBP (Great Britain), euro-EURO (European Monetary Union) and euro-JPY (Japan). The time period of the data set is May 1 2001 to May 1 2006. Purpose of this paper is to extend the study of global interest rates interrelationships with a technique which combines stationarity and cointegration tests, and use these technique as a basis for constructing an error correction model. Error correction model is applied to assess the existence of long-run equilibrium relationships among the time series data. The degree of interest rates linkages among offshore fund market is analyzed.